Implementasi Metode Resitasi Berbasis Teknologi Digital dalam Mengatasi Kesulitan Belajar Siswa pada Pembelajaran PAI - Yani Yani; Syafruddin Syafruddin; Sri Jamilah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to describe the implementation of a digital technology-based recitation method in addressing students’ learning difficulties in Islamic Religious Education (IRE) at Muhammadiyah High School in Bima City, as well as to analyze its supporting and inhibiting factors. The method used was qualitative descriptive, with data collection techniques including observation, in-depth interviews, and documentation. The results of the study indicate that the implementation of the digital technology-based recitation method was carried out through three structured stages: the planning stage, which included selecting platforms such as Google Classroom, WhatsApp Groups, and YouTube; the implementation stage, which involved assigning varied tasks such as watching videos, recording recitations, and digital presentations; and the evaluation and follow-up stage, which included rubric-based assessment and periodic feedback. Supporting factors include teachers’ willingness to learn technology, students’ enthusiasm, and school facility support. Meanwhile, inhibiting factors include teachers’ limited time to develop content, uneven digital competencies among teachers, internet connection stability, students’ limited data quotas, and the temptation to use social media or play games. This study concludes that the digital technology-based recitation method is effective in helping students overcome learning difficulties, increasing independence and responsibility, and fostering a deeper understanding of Islamic Education (PAI) material.